Penerapan Bentuk Dinamis Dalam Membangun Suasana Pada Ruang Tunggu RSUD Pandega Pangandaran - Siska Aprilia, Dhea (Dinasti Research, 2024)
The interior design of hospital waiting rooms plays a crucial role in providing comfort and reducing stress for patients and visitors. In a medical environment, the psychological and physical factors of waiting room design can significantly impact the overall user experience. This study aims to explore and implement dynamic design forms in the waiting room of RSUD Pandega Pangandaran to enhance user experience quality. The methodology employed in this research includes field observations to understand the existing conditions, in-depth interviews with users to identify their needs and preferences, and a comprehensive literature review on dynamic interior design, ergonomic principles, and environmental psychology theories. The findings of the study indicate that the use of dynamic forms, combined with soothing color elements, optimal natural and artificial lighting, and ergonomic and flexible furniture arrangements, can significantly improve the comfort and satisfaction of waiting room users. This study emphasizes the importance of a holistic approach in designing hospital waiting rooms that not only focuses on aesthetics but also on functional and psychological aspects to create a more humane environment that supports the healing process